AAGBS Annual Report 2021: at a glance (Bespoke@AAGBS) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
To offer courses that meet the needs of the participants, employers, industries which focus more on a particular set of skills on short period of time.